Urine caffeine concentration in doping control samples from 2004 to 2015 - Aguilar-Navarro, M.; Muñoz, G.; Salinero, J. J.; Muñoz-Guerra, J.; Fernández-Álvarez, M.; del Mar Plata, M.; Del Coso, J. (Nutrients, 2019)
The ergogenic effect of caffeine is well-established, but the extent of its consumption in sport is unknown at the present. The use of caffeine was considered "prohibited" until 2004, but this stimulant was moved from the List of Prohibited Substances to the Monitoring Program of the World Anti-Doping Agency to control its use by monitoring urinary caffeine concentration after competition. However, there is no updated information about the change in the use of caffeine as the result of its inclusion in the Monitoring Program. The aim of this study was to describe the changes in urine caffeine concentration from 2004 to 2015. A total of 7488 urine samples obtained in official competitions held in Spain and corresponding to athletes competing in Olympic sports (2788 in 2004, 2543 in 2008, and 2157 in 2015) were analyzed for urine caffeine concentration. The percentage of samples with detectable caffeine (i.e., >0.1 µg/mL) increased from ~70.1%, in 2004-2008 to 75.7% in 2015. The median urine caffeine concentration in 2015 (0.85 µg/mL) was higher when compared to the median value obtained in 2004 (0.70 µg/mL; p < 0.05) and in 2008 (0.70 µg/mL; p < 0.05). The urine caffeine concentration significantly increased from 2004 to 2015 in aquatics, athletics, boxing, judo, football, weightlifting, and rowing (p < 0.05). However, the sports with the highest urine caffeine concentration in 2015 were cycling, athletics, and rowing. In summary, the concentration of caffeine in the urine samples obtained after competition in Olympic sports in Spain increased from 2004 to 2015, particularly in some disciplines. These data indicate that the use of caffeine has slightly increased since its removal from the list of banned substances, but urine caffeine concentrations suggest that the use of caffeine is moderate in most sport specialties. Athletes of individual sports or athletes of sports with an aerobic-like nature are more prone to using caffeine in competition.